(untitled) (e-GiGi, 2025)
Abstract: Age estimation is an important part of forensic identification, and teeth are among the most reliable structures used for this purpose. One of the promising histological methods is tooth cementum annulation (TCA), which involves counting of incremental growth lines in the cementum to estimate chronological age. These cementum incremental lines formed through the rhythmic deposition of mineralized tissue, appear as alternating dark and light bands and are thought to reflect annual biological cycles. The constant and non-adaptive growth of acellular cementum is considered as the ideal part of cementum to be used in cementochronology analysis. Therefore, this study aimed to explore the principles, applications, and potential of TCA. Currently, TCA or cementochronology has been widely used as an age estimation method in the forensic field, but the results of existing studies to date vary due to different preparation techniques and analysis techniques. A standardized protocol for cementochronology has now been adopted in multiple studies, often conducted in ISO 9001-certified laboratories to ensure consistency in histological preparation. While this standardization has improved methodological reliability, further research is still needed to evaluate the accuracy and applicability of cementochronology for age-at-death estimation in various forensic contexts. However, its implementation in peripheral or resource-limited settings remains challenging, as the method is invasive, requires specialized equipment, and involves laboratory-based histological processing. This review highlights that these incremental lines, particularly in acellular cementum that formed consistently over time, show a strong correlation with chronological age. Tooth cementum annulation has shown promising results and is considered a valuable complementary method for forensic age estimation. Keywords: age estimation; tooth cementum annulation; cementochronology; forensic odontology